Keterlibatan Wanita Tani Pada Kegiatan Usahatani “Bawang Goreng Lokal Palu” Dalam Upaya Peningkatan Pendapatan Keluarga Di Kabupaten Donggala - Rosmini Rosmini (Agroland: Jurnal Ilmu-ilmu Pertanian, 2007)
The aim of the research was to identify the participation level of female farmers on the farming system of fried onion var. local Palu, activities dominantly carried out by the female farmers in the farming system, and their contribution to family incomes. The research used a Survey method with a descriptive analysis. Respondents were purposively determined based on the marital status of the female farmers as housewives who actively participate in the farming system activities. There were 4 research locations in where 10 respondents were taken from each location, thus in total there were 40 respondents. The results showed that there was no significant difference in the involvement of the female farmers on the farming system activities among the research locations except for Sidera area where the female farmer only carried out certain activities. The types of the farming system activities showing high involvement of the female farmer were planting, cleaning, and harvesting. The level of family incomes derived by the female farmers due to their involvement in the farming system activities was varied among the research locations. The largest income was generated by the female farmers in Guntarano which was IDR 763,875 per planting season followed by those in Wombo which was IDR 728,437. The income generated by the female farmers in Soulowe and Sidera was IDR 409,500 and IDR 389,812 per planting season, respectively.